ANALISIS KECELAKAAN KERJA PADA PEKERJA PENGELASAN DI CV. CAHAYA TIGA PUTRI - Rizka Pisceliya, Dwi Marina; Mindayani, Sri (Jurnal Riset Hesti Medan, 2018)
A work accident is an undesirable adverse event against a human, damaging property or disadvantage to the process. Data from the ILO in 2013 says that one worker die every 15 seconds due to workplace accidents. This study aims to analyze accidents in welding workers in CV. Cahaya Tiga Putri Kelurahan Sungai Sapih Kecamatan Kuranji Padang in 2017. The research design used was cross-sectional study. This research was conducted at CV. Cahaya Tiga Putri Padang located at Jalan Lolongkaran Sungai Sapih Padang in December to July 2017. The population of this research were welding workers. Samples were taken using total sampling technique, as many as 32 people. Data were analyzed univariat and bivariate with chi-square test. The result of the research shows that 46,9% of respondents have work accident, 53,1% of respondents have unsafe behavior, 53,1% of respondent have unsafe condition, 56,3% respondent have bad knowledge. From the statistical test results known there was a relationship between unsafe acts with work accidents, there was a relationship between unsafe conditions with work accidents and there was a relationship between knowledge with accidents. To reduce the number of occupational accidents, it is expected that workers should always working with using personal protective equipment (PPE), create a safe working environment and for the owner in order to improve worker knowledge by providing training and promotion of occupational health and safetty such as counseling about PPE.Key words : Work Accident, Unsafe Action, Unsafe Condition, Knowledge